Advances in pediatric video capsule endoscopy: current applications and future directions - Rojas, Isabel; Barth, Bradley A.; Stewart, Jeremy W. (Frontiers in Pediatrics, 2026)
Video capsule endoscopy (VCE) has revolutionized the evaluation of small bowel pathology, offering a safe, non-invasive, radiation-free diagnostic modality with broad clinical utility. Patency capsule use has further improved safety by minimizing the risk of retention in patients with suspected strictures. Since its introduction, its applications have expanded from obscure gastrointestinal bleeding and Crohn's disease to celiac disease, polyposis syndromes, and small bowel tumors among other indications. Emerging artificial intelligence (AI) integration promises to enhance diagnostic accuracy, streamline image analysis, and reduce interobserver variability. Furthermore, advancements in capsule design, including magnetic-assisted navigation and extended battery life, enable precise control and complete small bowel evaluation, even in cases of delayed gastrointestinal motility. High-definition imaging further allows for the identification of subtle mucosal abnormalities, such as vascular lesions, inflammation, and erosions, that might otherwise go undetected. Beyond diagnosis, novel applications, such as motility capsule studies and wireless capsule drug delivery systems, are unlocking new possibilities for functional and therapeutic interventions. Future innovations combining diagnostic and interventional capabilities promise to reduce the need for invasive procedures, optimize outcomes, and significantly enhance the quality of life for pediatric patients.